Tindak Pidana Pelanggaran Kesusilaan di Kepolisian Resor Karangasem - Agus Hindiana Christantino Mek; Anak Agung Sagung Laksmi Dewi; I Nyoman Subamia (Fakultas Hukum, Universitas Warmadewa, 2022)
Crimes and violations of decency such as adultery can cause trauma and mental damage to the victim, and often lead to physical violence if caught or the victim does not want to comply with the perpetrator's request to be ambiguous. Based on this background, the formulation of the problem is how to regulate the violation of decency at the Karangasem Resort Police and how to sanction the violation of decency at the Karangasem Resort Police. The research method used is data processing in normative law. To be able to find out what is included in the act of decency in the regulation of criminal law laws. So that if there is an immoral crime, there must be sanctions that ensnare the perpetrators of these crimes, which sanctions become a tool to guide the community so that it has a deterrent effect on the perpetrators of these crimes.